Case Report: Immune-Related Toxicity During Adjuvant Treatment With BRAF Plus MEK Inhibitors in a Melanoma Patient - Boutros, Andrea; Schiavi, Chiara; Cecchi, Federica; Spagnolo, Francesco; Guadagno, Antonio; Tanda, Enrica Teresa; Giusti, Francesca; Murdaca, Giuseppe; Queirolo, Paola (Frontiers in Immunology, 2020)
Adjuvant treatment of operated melanoma has deeply changed in the last few years with the introduction of immune-checkpoint inhibitors and BRAF/MEK inhibitors. Sarcoidosis is a systemic inflammatory disease causing non-caseous granulomatous reactions. Sarcoid-like granulomatous reactions have been reported in patients with advanced melanoma, mostly related to immunotherapy with immune-checkpoint inhibitors. We report a case of a 38-year-old woman with stage III operated melanoma treated with adjuvant BRAF plus MEK inhibitors, who developed sarcoidosis-like syndrome with systemic involvement, resolved after discontinuation of treatment. The occurrence of immune-related toxicity with the use of MAPK inhibitors supports the hypothesis that this class of drugs may also have an immunological effect, and that the long-term efficacy of adjuvant MAPK inhibitors may be due to their immunological function.